Pemanfaatan Media Sosial Dalam Meningkatkan Efektivitas Pemasaran E-Commerce - Salsa Cintya Bella; Lyra Nabila Putri; Erine Dheanda Absyarina (Jurnal Cakrawala Informasi, 2025)
The development of information technology has significantly transformed the business world, particularly in the e-commerce sector. Social media has become one of the most effective tools in digital marketing strategies. This study aims to explore how social media utilization can enhance marketing effectiveness in e-commerce. Using a qualitative descriptive approach, this study analyzes various social media platforms such as Instagram, Facebook, TikTok, and Twitter employed by e-commerce businesses to reach consumers more broadly and personally. The findings show that social media enhances direct interaction between sellers and customers, broadens market reach, and builds brand loyalty through engaging content and effective communication strategies. Furthermore, features such as paid advertising and influencer marketing have proven to significantly boost sales conversion. The study concludes that strategic use of social media has a positive impact on e-commerce marketing effectiveness, particularly in increasing brand visibility, consumer engagement, and product sales..